Tree Pollination Under Global Climate Change - Ramírez, Fernando (SpringerBriefs in Agriculture,, 2018)
This brief reviews the pollination aspects of both wild and domesticated fruit tree species in a global climate change context. It explores cross-pollination mediated by insects, vertebrates and abiotic factors, self-pollination and their global warming implications. The authors identify the link between abiotic factors such as precipitation and severe droughts in the context of tree pollination and climate change. Furthermore, pollination and conservation implications in agriculture as well as wild tree populations are explored. Emphasis has been given to fruit trees growing in tropical, subtropical and temperate environments.